2007
DOI: 10.1007/s00213-007-0856-2
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the mGlu7 receptor elicits antidepressant-like effects in mice

Abstract: These results strongly suggest that activation of the mGlu7 receptor elicits antidepressant-like effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(80 citation statements)
references
References 38 publications
5
74
0
1
Order By: Relevance
“…This suggests that AMN082 may have effects that are distinct from its purported selective activation of autoreceptors, which should decrease glutamate release. Second, a major dilemma in interpreting the effects of AMN082 is that comparable doses to those used in the present study were recently shown to produce body tremors and locomotor deficits in mGluR7 knockout mice (Palucha et al, 2007). Thus, despite a very thorough receptor-binding analysis during its initial identification (Mitsukawa et al, 2005) these findings strongly suggest that off-target actions of AMN082 may be responsible for the effects observed in the present study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This suggests that AMN082 may have effects that are distinct from its purported selective activation of autoreceptors, which should decrease glutamate release. Second, a major dilemma in interpreting the effects of AMN082 is that comparable doses to those used in the present study were recently shown to produce body tremors and locomotor deficits in mGluR7 knockout mice (Palucha et al, 2007). Thus, despite a very thorough receptor-binding analysis during its initial identification (Mitsukawa et al, 2005) these findings strongly suggest that off-target actions of AMN082 may be responsible for the effects observed in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…AMN082 is orally active and crosses the blood brain barrier making it ideal for in vivo analysis (Mitsukawa et al, 2005). Acute AMN082 administration has antidepressant-like effects in the tail-suspension and forced swim tests (Palucha et al, 2007). However, there are no published studies of the effects of AMN082 addictive behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, N,N'-dibenzhydrylethane-1,2-diamine dihydrochloride (AMN082), an allosteric mGlu7 receptor agonist, exhibited antidepressant effects in forced swim and tail suspension tests [97]. The antidepressant effect of AMN082 was not observed in knockout mice lacking mGlu7 receptors, showing that AMN082 exerted its effect through mGlu7 receptor activation.…”
Section: Mglu7 Receptor Ligandsmentioning
confidence: 99%
“…In any case, the combination of inhibition of fear acquisition and the facilitation of its extinction predicts anxiolytic effects of AMN082, which were actually found by Stachowicz et al (2008) in wildtype, but not in mGlu7 receptor knockout mice. Likewise, antidepressant activity was seen with AMN082 administered intraperitoneally in the forced swim and the tail suspension tests only in wild type but not in mice lacking mGlu7 receptors (Palucha et al, 2007). However, significant inhibition of spontaneous locomotion was observed at higher doses of AMN082 also in knockout animals, suggesting off-target effects of the compound.…”
mentioning
confidence: 95%